Hydrogen embrittlement characteristics of two tempered martensitic steel alloys for high-strength bolting. (September 2017) - Brahimi, SV; Sriraman, KR; Yue, S
Hydrogen embrittlement threshold curves were derived for two quenched and tempered steel grades, AISI 4135 and AISI 4340, at varying hardness ranging from 33 to 54 HRC. For each material, hydrogen was introduced (i) by zinc electroplating as a worst case condition for internal hydrogen embrittlement and (ii) by imposing cathodic potential of −1.2 V as a worst case condition for environmental hydrogen embrittlement. Overall, AISI 4135 exhibited lower thresholds than AISI 4340, making it the more susceptible of the two alloys. The findings demonstrate although hardness and/or strength have a first-order effect on hydrogen embrittlement susceptibility, difference in chemistry leading to differences microstructural characteristics must also be considered. Below hardness of 39 HRC, both alloys were not susceptible to internal hydrogen embrittlement, a finding that is consistent with common industry practice and fastener electroplating standards that do not mandate baking of electroplated fasteners with specified hardness below 39 HRC.